Children's perspectives and experiences of the COVID‐19 pandemic and UK public health measures. (8th September 2021) - Thompson, Jill; Spencer, Grace; Curtis, Penny
Abstract: Background: The COVID‐19 pandemic has had profound impacts on how we live our lives; yet, the implications for children and the effects on children's everyday lives have been relatively underacknowledged. Understanding children's views on COVID‐19 and related restrictions on their lives provides an important opportunity to understand how children have responded to the pandemic, including the impacts on their social and emotional well‐being. Objective: This study explored the experiences and perspectives of children in relation to the COVID‐19 pandemic and related restrictions on everyday life. Method: A qualitative study using semistructured online interviews with participatory drawings was undertaken between May and July 2020. Eighteen children from England and Wales, aged 7–11 years, participated in interviews. Findings: Themes included children's reflections on (1) COVID‐19 as a deadly contagion; (2) fears and sadness and (3) social responsibility and opportunities to respond positively. Conclusions: Young children offer insightful reflections on their experiences during the first wave of the COVID‐19 pandemic in the United Kingdom. Children and young people's perspectives must be considered in future public health discourse. Patient or Public Contribution: This work was informed by conversations with my own three primary school‐aged children and the children of friends. A formal Patient and Public Involvement (PPI) group was not established due to the speed with which the project was undertaken. Any future research in this area would benefit from formal PPI in the design, methods and questions.